2018
DOI: 10.1103/physrevlett.120.103202
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for Testing Lorentz Invariance with Atomic Systems

Abstract: We describe a broadly applicable experimental proposal to search for the violation of local Lorentz invariance (LLI) with atomic systems. The new scheme uses dynamic decoupling and can be implemented in current atomic clock experiments, with both single ions and arrays of neutral atoms. Moreover, the scheme can be performed on systems with no optical transitions, and therefore it is also applicable to highly charged ions which exhibit a particularly high sensitivity to Lorentz invariance violation. We show the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 40 publications
(71 reference statements)
1
96
1
1
Order By: Relevance
“…Again, the sign is opposite to Yb E3, making their comparison more powerful and improving the control of potential systematic effects. Furthermore, the value compares well with other HCI 30 .…”
Section: Resultssupporting
confidence: 73%
“…Again, the sign is opposite to Yb E3, making their comparison more powerful and improving the control of potential systematic effects. Furthermore, the value compares well with other HCI 30 .…”
Section: Resultssupporting
confidence: 73%
“…This approach combines advantages of unprecedented frequency stability of optical lattice clocks on neutral atoms and low sensitivity to BBR of ion optical clocks. Moreover, precision spectroscopy in Tm opens possibilities for sensitive tests of Lorentz invariance 5 and for a search of the fine structure constant variation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, HCI can be used to search for such variations and to test predictions of this class of theoretical models of dark matter. Recently, HCI have also been identified as potential candidates for significant improvement for tests of Lorentz symmetry (Shaniv et al, 2017). New experimental techniques for HCI described in this review combined with an improved theoretical description will allow for more stringent QED tests.…”
Section: B Atomic Physics At the Extremes: Highly Charged Ionsmentioning
confidence: 98%
“…Further significant improvement of the LV constraints with such experiments requires another system with a long-lived or ground state that has a large j|T (2) 0 |j matrix element. ; Shaniv et al (2017) calculated this matrix element in a variety of systems and identified the 4f 13 6s 2 2 F 7/2 state of Yb + and HCI as systems with large sensitivities to LLI. HCI ions of interest are among those already proposed for the tests of the α-variation.…”
Section: A Tests Of Local Lorentz Invariancementioning
confidence: 99%
See 1 more Smart Citation